Estudo comparativo de diferentes métodos de alinhamento no eletrocardiograma de alta resolução - Monteiro, Diogo Marques (2017)
The classical highresolution electrocardiogram is characterized by the use of alignment techniques and coherent mean for correct identification of high-frequency and low-amplitude signals, covered by interference. The optimization of the alignment method attenuates the effects of low pass filtering caused by alignment errors (AE), allowing the analysis of ventricular activation late potentials present in the QRS complex. A comparative study was carried out between three methods of alignment, level detector, normalized integral and double integration, aiming at performance evaluation by parameter analysis, such as alignment error and baseline noise. Results shows that all three methods are suitable to reduce the alignment error. The Simson bidirectional filter was also compared with the bidirectional filter applied to whole signals, in the process of obtaining the Vector Magnitude, through the parameters dQRS, LAS40 and RMS40. Signals from a database were divided into two groups, one composed of healthy individuals, the control group, and the other composed of individuals with cardiac pathology, the sick group. Some differences were found, including a significant difference in QRS duration (p < 0.05), but further study is still necessary, with the use of more signals for more robust results. A direction of how ECGAR may be used depending on the type of cardiac signal being treated is indicated.